Stark-assisted quantum confinement of wavepackets: a coupling of nonadiabatic interaction and CW-laser - Arasaki, Yasuki; Mizuno, Yuta; Scheit, Simona; Takatsuka, Kazuo (The journal of chemical physics, 2016)
When a nonadiabatic system that has an ionic state (large dipole moment) and a covalent state (small dipole moment) is located in a strong laser field, the crossing point of the two potential energy curves is forced to oscillate due to the oscillating laser field and to meet wavepackets moving on the potential curves many times. This leads to additional transitions between the two states, and under favorable conditions, the wavepacket may be confined in a spatial region rich in nonadiabatic interaction. In this paper, taking the LiF molecule system in a continuous-wave driving field as a prototypical example, the dynamical origins of the wavepacket confinement are theoretically investigated.